IMPROVING THE INTEGRATION OF INSURANCE COMPANIES AND COMMERCIAL BANKS (American Journal of Interdisciplinary Research and Development, 2023)
The article presents the economic essence of the process of integration of insurance companies and commercial banks, their classification, and analysis of mutual cooperation between insurance companies and commercial banks. The advantages of cooperation between insurance companies and commercial banks, as well as the classification criteria for bancassurance and international legal norms were also studied.